"Office Hours are Kind of Weird": Reclaiming a Resource to Foster Student-Faculty Interaction - Margaret Smith; Yujie Chen; Rachel Berndtson; Kristen M. Burson; Whitney Griffin (Park University, 2017)
Office hours reserve time and space for student-faculty interaction, a benchmark for engaging students in educationally purposive activities. Our study finds a mismatch between the institutionally intended purpose of office hours and student perceptions of office hours. We examine student perceptions of office hours with results from a survey administered at a public research institution. We conclude that it is necessary for institutions - large public research institutions, particularly - to do more to demonstrate to students the value for interacting with faculty and to consistently support the development of relationships between undergraduates and those who teach them.